GRWR Correlates with the Metabolism of Tacrolimus after Pediatric Living Donor Liver Transplantation According to Donor CYP3A5 Polymorphism. (30th October 2022) - Wan, Ping; Hou, Yuchen; Qiu, Bijun; Feng, Mingxuan; Yang, Taihua; Luo, Yi; Xia, Lei; Chen, Xiaosong; Zhang, Jianjun; Xue, Feng; Xia, Qiang
Abstract : Objectives . Tacrolimus is characterized by high pharmacokinetic variability in combination with a narrow therapeutic range. However, influence of donor CYP3A5 genotype and graft-to-recipient body weight ratio (GRWR) on tacrolimus' pharmacokinetics after pediatric living donor liver transplantation (LDLT) remains unclear. Methods . A total of 174 LDLT recipients (<6 y) were grouped according to donor CYP3A5 genotypes (nonexpressor (NEX) or expressor (EX)) and GRWR (<3.0% (SS, small-size) or ≥3.0% (LS, large-size)): SS/NEX (n = 40 ), SS/EX (n = 38 ), LS/NEX (n = 48 ), and LS/EX (n = 48 ). Pharmacokinetics of tacrolimus and clinical outcomes were analyzed. Results . The relationships between the concentration-dose ratio and donor CYP3A5 genotypes and graft size were examined 3, 7, 14, and 30 days after the transplantation. Tacrolimus C0 levels varied greatly among groups, although recipients started with the same initial dosage. LS/EX recipients had significantly lower C0 levels in comparison with those of other groups. The use of CYP3A5-EX-grafts and a greater GRWR both resulted in significantly higher TAC dose requirements and lower C/D ratios. However, the significance of GRWR no longer exists 3 months after transplantation. The multivariate generalized linear mixed model analysis showed that donor CYP3A5 genotypes (F = 11.876 ; P = 0.01 ) and GRWR (F = 4.631 ; P = 0.033 ) were independent impact factors for C/D ratios 3, 7, 14, and 30 days after transplantation. Donor CYP3A5-EX genotype was associated with significantly increasing risks of infectious complications and significantly lower Cylex ATP values. However, no significant difference was observed in acute rejections among 4 groups. Conclusions . Monitoring of C0 levels alone is not reliable to guide tacrolimus administration. Donor CYP3A5 and GRWR both significantly affect tacrolimus pharmacokinetics after pediatric LDLT. The use of Cylex ATP tests would be helpful to avoid overimmunosuppression.